Effect of Extruding Full-Fat Soy Flakes on Trans Fat Content - Hongxia Feng; Xiaonan Sui; Yunhe Chang; Baokun Qi; Yan Zhang; Yang Li; Lianzhou Jiang (The Scientific World Journal)
To evaluate the effects of extrusion process on the trans fatty acids (TFAs) formation in soybean crude oils, three different extrusion parameters, namely, extrusion temperature (80–160°C), feed moisture (10–26%), and screw speed (100–500 rpm), were carried out. It was found that only five different types of TFAs were detected out using gas chromatography-mass spectrometry. Before the extrusion started, the initial amount of total TFAs was 3.04 g/100 g. However, after extruding under every level of any variable, the total amounts of TFAs were significantly higher than those in the control sample (P<0.05). For example, taking the effect of extrusion temperature into account, we can find that the highest amount of total of trans fatty acid (TTFA) was 1.62 times the amount of that in the control sample, whereas the lowest amount of TTFA was 1.54 times the amount of that in the control sample. Importantly, it was observed that the amounts of every type of trans fatty acid were not continuously increasing with the increase of the level of any extrusion variable. This phenomenon demonstrated that the formation and diversification were intricate during extruding process and need to be further studied.